The Government's Realization in Environmental Law Enforcement is Reviewed from The Indonesian State Administrative Law - Mariska Jasiaat; Rike Ayu Pinastiya Dinar Anggraini; Khansa Adelia Labibah; Nunik Nurhayati; Moh. Indra Bangsawan (Proceeding International Conference Restructuring and Transforming Law, 2024)
The environmental sector is affected by globalization. Indonesia is one of the countries affected by globalization, which results in pollution and degradation of local ecology. Therefore, the government enacted laws, especially Law Number 32 of 2009, which addresses and regulates issues related to environmental protection and management. The author uses a normative juridical analysis approach to determine government accountability and the implementation of Law No. 32 of 2009 through juridical review. The Central Government and Local Government have the responsibility to protect the environment, as stipulated in Law Number 32 of 2009 concerning Environmental Protection and Management. Article 63 of Law Number 32 of 2009 stipulates the responsibilities and authorities of the Central Government and Regional Government. There are two different approaches to prevention: preventive measures and repressive efforts. Environmental law enforcement administratively seeks to avoid pollution and environmental damage, while at the same time seeking to punish those responsible for environmental pollution and damage.